2006
DOI: 10.1159/000088018
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Receptor Expressions and Proliferation Markers in Postmenopausal Endometrial Polyps

Abstract: Background/Aims: Endometrial polyps are quite common in the general population, they have a significant role in postmenopausal bleeding, and the pathogenesis is unclear. The aim of this study was to investigate proliferation markers and expression of estrogen and progesterone receptors in endometrial polyps in postmenopausal women. Methods: Endometrial polyps were removed by hysteroscopy from 36 women who presented with postmenopausal bleeding. None were using hormonal therapy. The control group consisted of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
4
23
2
3
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17] In this study, the obesity prevalence in cervical group and control group was 32 (1%), and 23 (7%), respectively. Obese women have also a higher risk of insulin resistance, hyperinsulinemia and hyperandrogenemia.…”
Section: Discussionmentioning
confidence: 50%
“…[8][9][10][11][12][13][14][15][16][17] In this study, the obesity prevalence in cervical group and control group was 32 (1%), and 23 (7%), respectively. Obese women have also a higher risk of insulin resistance, hyperinsulinemia and hyperandrogenemia.…”
Section: Discussionmentioning
confidence: 50%
“…The balance between mitotic activity and apoptosis is considered to regulate normal endometrial development during the menstrual cycle, and disturbances of these physiological processes have been proposed to occur in endometrial polyps (Stewart et al 1999 ). Oestrogen and progesterone act, via their receptors, as modulators of proliferation and differentiation in the normal endometrium (Inceboz et al 2006 ). Both oestrogen and progesterone receptors have been identifi ed in the glandular epithelium of endometrial polyps in both post-and premenopausal women, but the receptor expression appears to be disorderly compared with normal endometrium (Lopes et al 2007 ;Ryan et al 2005 ;Mittal et al 1996 ;McGurgan et al 2006a ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Both oestrogen and progesterone receptors have been identifi ed in the glandular epithelium of endometrial polyps in both post-and premenopausal women, but the receptor expression appears to be disorderly compared with normal endometrium (Lopes et al 2007 ;Ryan et al 2005 ;Mittal et al 1996 ;McGurgan et al 2006a ). Furthermore, demonstrations of increased levels of Ki61, a marker of cell proliferation, and Bcl-2, an inhibitor of apoptosis, indicate that loss of usual control mechanisms for growth may be of importance in development of endometrial polyps (Inceboz et al 2006 ;McGurgan et al 2006a ;Maia et al 2004a ;Mertens et al 2002 ;Taylor et al 2003 ). This loss of proapoptotic mechanisms may be related to unopposed hyperestrogenism, because Bcl-2 expression increases in response to oestrogen (Mertens et al 2002 ;Dahmoun et al 1999 ).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated a higher ER expression in the epithelium and stroma of the endometrial polyps from menopausal patients Differences in estrogen and progesterone receptor expression in endometrial polyps and atrophic endometrium of postmenopausal women with and without exposure to tamoxifen in comparison to the adjacent atrophic endometrium (17)(18)(19). With regard to the expression of PR, previous studies have demonstrated a higher expression in the epithelium and not the stroma of the polyp, compared to the adjacent atrophic endometrium (17)(18)(19)(20). This finding suggests that endometrial polyps have a higher sensitivity to estrogen and progesterone and may develop even in the presence of low serum hormone concentrations (19).…”
Section: Introductionmentioning
confidence: 99%